Pengaruh Disiplin Kerja Motivasi Ekstrinsik Dan Kompensasi Terhadap Kinerja Karyawan Pada Brilliant English Course Pare - Octa Krisdiyanti; Debby Santyo Rusandy; Iing Sri Hardiningrum (Manajemen Kreatif Jurnal, 2023)
This study discusses the effect of work discipline, job satisfaction and physical work environment on employee performance at the Brilliant English Course Pare, Kediri Regency. This study aims to determine and explain the results of the influence of work discipline, extrinsic motivation and compensation on employee performance at the Brilliant English Course Pare, Kediri Regency. The sample of this research is all employees who are in the office, namely as many as 30 employees. The sampling technique was carried out using the saturated sample type method, namely non-probability sampling. The analysis technique used is the classical assumption, multiple linear regression. The results of this study are that there is a positive and significant effect of work discipline on employee performance with a significant value of 0.02 <0.05. There is a positive and significant influence of extrinsic motivation on employee performance with a significant value of 0.02 <0.05. There is a positive and significant effect of compensation on employee performance with a significant value of 0.000 <0.05. There is the influence of work discipline, extrinsic motivation and compensation simultaneously on employee performance with a significant value of 0.000 <0.05.